Regulation of G6PD acetylation by SIRT2 and KAT9 modulates NADPH homeostasis and cell survival during oxidative stress - Wang, Yi‐Ping; Zhou, Li‐Sha; Zhao, Yu‐Zheng; Wang, Shi‐Wen; Chen, Lei‐Lei; Liu, Li‐Xia; Ling, Zhi‐Qiang; Hu, Fu‐Jun; Sun, Yi‐Ping; Zhang, Jing‐Ye; Yang, Chen; Yang, Yi; et al. (The EMBO journal, 2014)
Glucose‐6‐phosphate dehydrogenase (G6PD) is a key enzyme in the pentose phosphate pathway (PPP) and plays an essential role in the oxidative stress response by producing NADPH, the main intracellular reductant. G6PD deficiency is the most common human enzyme defect, affecting more than 400 million people worldwide. Here, we show that G6PD is negatively regulated by acetylation on lysine 403 (K403), an evolutionarily conserved residue. The K403 acetylated G6PD is incapable of forming active dimers and displays a complete loss of activity. Knockdown of G6PD sensitizes cells to oxidative stress, and re‐expression of wild‐type G6PD, but not the K403 acetylation mimetic mutant, rescues cells from oxidative injury. Moreover, we show that cells sense extracellular oxidative stimuli to decrease G6PD acetylation in a SIRT2‐dependent manner. The SIRT2‐mediated deacetylation and activation of G6PD stimulates PPP to supply cytosolic NADPH to counteract oxidative damage and protect mouse erythrocytes. We also identified KAT9/ELP3 as a potential acetyltransferase of G6PD. Our study uncovers a previously unknown mechanism by which acetylation negatively regulates G6PD activity to maintain cellular NADPH homeostasis during oxidative stress. Synopsis The pentose phosphate pathway plays an important role in the oxidative stress response by supplying the reductant NADPH. SIRT2‐mediated deacetylation and activation of the glucose‐6‐phosphate dehydrogenase, the rate‐limiting enzyme in this pathway, stimulates the production of cytosolic NADPH to counteract oxidative damage. K403 acetylation decreases G6PD activity by inhibiting dimer formation. SIRT2 and KAT9/ELP3 regulate G6PD K403 acetylation. Regulation of G6PD K403 acetylation modulates NADPH homeostasis and cell survival during oxidative stress. Graphical Abstract Following oxidative stress, production of the reductant NADPH via the pentose phosphate pathway is stimulated by SIRT2‐mediated deacetylation and activation of G6PD.